Dampak Nikah Siri Terhadap Disregulasi Emosi dan Fungsi Kognitif Perempuan: Tinjauan Neuropsikologi dan Kesetaraan Jender Perspektif Qasim Amin - Mastur, Mastur; Us’an, Us’an; Waldiono, Jenjang (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Unregistered marriage is a social phenomenon that is still prevalent in Indonesia, despite causing various problems, especially for women. This study examines how the practice of unregistered marriage triggers emotional dysregulation such as anxiety and confusion in women, which then impacts their cognitive function. Using a neuropsychological approach and Qasim Amin's gender equality perspective, this study analyzes the complex relationship between unstable emotional conditions due to marital uncertainty and decreased cognitive capacity in women. The research method used is a qualitative literature study with document analysis from various literature on neuropsychology, psychology, Islamic family law, and Qasim Amin's thoughts. The results show that unregistered marriage creates a state of chronic stress in women that triggers emotional dysregulation, which in turn disrupts cognitive functions such as memory, concentration, and decision-making. Qasim Amin's equality perspective emphasizes that the practice of unregistered marriage contradicts the principles of dignity and justice for women. This study recommends the need for psychological and legal education for the community, as well as strengthening the perspective of gender equality in Islamic studies.